The Effect of Low Frequency Sound on Heart Rate Variability and Subjective Perception: A Randomized Crossover Study - Vilímek, Zdeněk; Kantor, Jiří; Krejčí, Jakub; Janečka, Zbyněk; Jedličková, Zuzana; Nekardová, Anna; Botek, Michal; Bucharová, Monika; Campbell, Elsa A (Healthcare (Basel, Switzerland), 2022)
BACKGROUND: Vibroacoustic therapy (VAT) uses low-frequency sound, often combined with listening to music, for therapeutic purposes. However, the impact of low-frequency vibration (LFV) on physiological functions and subjective perception is relatively unknown. METHODS: We conducted a randomized cross-over study with the aim of comparing the effect of constant LFV of 40 Hz, its amplitude modulation, and the placebo condition on heart rate variability (HRV), stress perception (measured by visual analogue scales for stress) and mood (measured by UWIST Mood Adjective Check List). RESULTS: Research experiments with various interventions (constant LFV with sound of nature (river in forest), amplitude modulation of the same LFV with sounds of nature and sounds of nature without LFV) were realised involving 24 participants. It was found there was an effect on HRV, stress perception and mood after the interventions. However, there were only seldomly experienced, and mostly nonsignificant, differences between the intervention conditions, so the effects may be attributed to factors other than LFV. CONCLUSIONS: Large scale experimental studies are needed to verify the preliminary findings and to explore various coinciding factors that may have influenced the results of this study, e.g., type of autonomic nervous system. We propose that the effect of LFV exposure may differ when combined with listening to music, and this hypothesis should be investigated in future studies.
Keywords: low frequency vibration; vibroacoustic therapy; heart rate variability; subjective perception; mood; nature sound; stress; cardiac autonomic regulation